2017
DOI: 10.1097/pec.0000000000001045
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Characteristics of Pediatric Trauma Patients Receiving Prehospital Care in Kigali, Rwanda

Abstract: Background Pediatric trauma is a significant public health problem in resource-constrained settings; however, the epidemiology of injuries is poorly defined in Rwanda. This study describes the characteristics of pediatric trauma patients transported to the emergency department (ED) of the Centre Hospitalier Universitaire de Kigali by emergency medical services in Kigali, Rwanda. Methods This cohort study was conducted at the Centre Hospitalier Universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Cases were identified and data were queried from institutional records via protocolised methods, as previously described [25] , [26] , [27] , [28] . Briefly, using a multipoint composite index generated from an electronic hospital database, all EC cases during each month of the accruement periods were identified.…”
Section: Methodsmentioning
confidence: 99%
“…Cases were identified and data were queried from institutional records via protocolised methods, as previously described [25] , [26] , [27] , [28] . Briefly, using a multipoint composite index generated from an electronic hospital database, all EC cases during each month of the accruement periods were identified.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, this study recommended establishment of effective measures for management of these injuries. 12 This was also emphasized by Stephens et al 13 through a study done in Uganda that limited resources settings significantly affect management of lower limb injury specifically femur and tibia fractures, as the study resulted in showing that volumes of cases outweighed available resources. 13 Although a little is known about the pattern of injury in our region, there was a report in Rwanda where 7% of surgical admissions were due to injury; moreover, Yamuragiye et al, 1 through a retrospective descriptive study, reported RTIs to be the main cause of injury and also reported that young males were the most vulnerable group.…”
Section: Resultsmentioning
confidence: 95%
“…In Rwanda, a study done by Aluisio et al 12 demonstrated that limb trauma followed by head injury were the prevalent pediatric injuries received. Moreover, this study recommended establishment of effective measures for management of these injuries.…”
Section: Resultsmentioning
confidence: 99%
“…SAMU has 70 employees including staff, dispatchers, Basic Life Support (BLS)trained drivers, Advanced Cardiovascular Life Support (ACLS)/BLS-trained nurses and non-physician anaesthetists. They offer emergency transportation throughout Rwanda and interventional care in Kigali, including stabilisation of patients, provision of life saving interventions and emergent transportation to the nearest healthcare facility 5–7…”
Section: Methodsmentioning
confidence: 99%
“…One study in Rwanda showed that children represented approximately 8% of all injured patients seen in the prehospital setting in Kigali 6. A study including 64 paediatric trauma cases found that the most common injuries involved the head and extremities 7. Both studies, however, had small sample sizes and lacked description of the mechanism of injury, acuity and management.…”
Section: Introductionmentioning
confidence: 99%